(untitled) (Journal of Science and Technology, 2016)
During a one-year study period cases referred to the Komfo Anokye Teaching Hospital Clinical Microbiology laboratory with the diagnoses, acute urethritis, pelvic peritonitis, sticky eyes, Ophthaimia is pepnalpnim or vulvo-vaginitis, were examined for penicillinase producing Neisseria gonorrhoeic (PPNG). In all 116 (0:0%) N, gonorrhoeic strains were isolated from a total of 168 cases examined. Of the 116 culture-positive N. gonorrhea isolated, 106 were tested for beta-lactamase activity and 95 (89.6%) were found to be penicillinase producing N. gonorrhoeae (PPNG) strains. Six ty-seven (67) of the 95 PPNGs were from males and twenty-eight (28) were from females. Among the latter were 2 (two) from children aged 10 and 12 years, Urethral discharge from a 65-year-old female also yielded PPNG. A number of the PPNG strains were not only resistant to penicillin but to other antimicrobial agents as well including tetracycline, chloramphenicol and co-trimoxazole. The highest PPNG rate was re-corded for the age group 16 through 30 years, with the age group 21 - 30 years topping the scale. These findings have grave public health implications not only for the pregnant woman and the neonate but also for the entire community. On the strength of our findings, it is suggested that the recommended (Ghana Ministry of Health) treatment regimen for gonococcal infections should be revised and that spectinom y-cin should be prescribed when absolutely necessary in order to for stall resistance development to the drug.